IMPORTANCE OF RAKTAVAHA SROTAS IN MANAGEMENT OF SKIN DISEASES - Hartalkar Jayant Subhash; Shreya Umesh Sawant (International Journal of Applied Ayurved Research, 2017)
The Nidan described regarding Kushtha can be divided into sharirik (mainly Pitta Vardhak Ahar, Vihar) and Manasik (Bhaya, Krodha, Santap ) leading to formation of Sama Pitta which ultimately leads to formation of Sama Rasa Dhatu alongwith Kapha and Vata. Pitta is Saman Guna Bhuista (similar in nature) to Rakta Dhatu so it is vitiated more. Due to vitiated Pitta there is altered Ranjan karma (Colouration) of Rasa Dhatu in Yakrit & Pleeha leading to formation Dusta Rakta Dhatu. The Dusta Rakta circulates all over the body through Raktavaha Srotas (involving Mansavaha & Ambuvaha also) leading to production of Kushtha (skin disorder). As Yakrit (liver) and Pleeha (Spleen) are the Mulas (root) of Raktavaha srotas (Blood circulatory channels), medicines which mainly acts on Yakrit gives good results in skin diseases. Since the period of our samhitas it is being adapted by Ayurvedic Physicians. Patient of Facial melanosis, leucoderma and psoriasis treated successfully by following the same concept are presented in this study.